STRATEGI PENDIDIKAN UNTUK MELESTARIKAN ARSITEKTUR TRADISIONAL DALAM RANGKA MEMPERKUAT JATI DIRl BANGSA - Sumarjo H, Sumarjo H (Jurnal Cakrawala Pendidikan, 2016)
Whether is it reconized or not, architecture works reflex cultural characteristic of people who have built them. Phenomena existing at the city and a part the village, many buildings of traditional house were demolished to substitute them for the new building of ’modern’ style. Undirected application of foreign culture elements can cause elimination of nation cultural values which will eventually weaken the personality and spirit of nationalism. Indonesian b-aditional architecture that has long time established evolutively is a shining example enriched with nation culture values. Physical f m , lay out, structure, and vatiations in traditional a r c h i t e m reflex the values of religion, social, economy, solidarity, technology and art. Superiority in Indonesian traditional architecture lies on the strength the values of religion, social and art. The all three values constitute the identity of nation culture The educational strategy of traditional architecture through formal and nonformal educations. rn formal education include in the subject matter curriculum. in nonfonnal educations thmugh semi tan tradition norm revitalism and permission to built